Kajian Kewenangan Kepala Daerah dalam Pemberian Izin Pertambangan di Kalimantan Timur - Tohari, Aulia Rahman; Indrayanti, Kadek Wiwik (Postgraduate University of Merdeka Malang, 2023)
This article identifies and analyzes the authority of provincial regionalgovernments in issuing mining permits based on Law Number 23 of 2014concerning Regional Government and Abuse of authority by Provincial Regional Governments in issuing mining business permits. The research method used is a normative legal research method. The results show that the authority to issue mining permits based on Law Number 23 of 2014 concerning Regional. Government is divided between the Regional Government and the Provincial Government. The authority to issue mining permits based on the concept of regional autonomy is more appropriate if it is owned by the regional government because the local government understands and knows their respective regions better. Furthermore, regarding licensing in the mineral and coal mining sector in the era of regional autonomy with the issuance of Law Number 22 of 1999 and updated with Law Number 32 of 2004 concerning Regional Government, Law Number 11 of 1967 concerning the principal principles of mining was originally is centralized and then adapts to the Regional Government Law to become decentralized. So that the government’s policy on licensing aspects in the mining sector in its implementation becomes overlapping between the authority of the Minister and the authority of the regent in granting permits for mining activities, resulting in misuse by the mining permit mafia by buying and selling permits, which in the end many permits are issued without following forest protection or sustainability rules. environment.